LB02.08: PREDICTORS OF RECURRENCE OF PHEOCHROMOCYTOMAS/PARAGANGLIOMAS. (June 2015) - Caprino, M. Parasiliti; Lucatello, B.; Bima, C.; D'Angelo, V.; Burrello, J.; Piovesan, A.; La Grotta, A.; Giordano, R.; Mulatero, P.; Veglio, F.; Arvat, E.; Ghigo, E.; et al.
Abstract : Objective: Pheochromocytomas and paragangliomas (PPGLs) are rare neoplasms often releasing cathecolamines, mainly originating from adrenals but occasionally observed in sympathetic and parasympathetic ganglia, with a genetic base up to 25% of the cases. After radical surgery of these tumors, disease recurrence was believed to be under 10% but recent studies reported a higher rate even after many years. Apart from familiar forms, little evidence exist about predictors of disease relapse, so we aimed to research predictors of recurrence with a retrospective analysis on patients referred to our Centers from 2000. Design and method: We collected data of patients with diagnosis of PPGL that underwent radical surgery. 76 subjects were recorded (Men/women: 42/34, Age: 45.9 ± 16.2 years) for a mean follow up of 64.9 ± 66.5 months. Genetic test for mutation of known susceptibility genes was performed in 37 cases, resulting positive in 23. Results: 20/76 (26.3%) patients had disease recurrence. These patients were younger (30.7 ± 14.8 vs 51.4 ± 12.9 years; p = 0.000), had higher rate of positive familiarity and genetic mutations (53.3% vs 13.0%; p = 0.002 and 75% vs 14.3%; p = 0.000, respectively), lower rate of abnormal metanephrines levels (27.3% vs 64.4%, p = 0.003), larger tumors (72.4 ± 37.6 vs 45.3 ± 20.2 mm; p = 0.000) and lower biochemical normalization rate (66.6% vs 96.3%, p = 0.004). We also analysed data on follow-up with Kaplan Meier curves, searching for variables associated with cumulative incidence of recurrence by Log Rank test: age at diagnosis < 45 years (p = 0.003), neoplasm dimension > 40 mm (p = 0.009), positive familiarity (p = 0.007) or genetic test (p = 0.000) and lack of biochemical normalization after surgery (p = 0.004) were associated to disease recurrence. Conclusions: Recurrence in PPGLs develops more frequently in young subjects, in patients with mutations in susceptibility genes, larger tumors, normal levels of metanephrines and incomplete normalization of biochemical markers after radical surgery. Patients with these characteristics should be monitored with strictly follow-up.